THE RELATIONSHIP BETWEEN LINGUISTIC IMAGES AND COGNITIVE CONCEPTS - Ulugova Shokhida Shokhrukhovna (Research Focus International Scientific Journal, 2025)
This article explores the relationship between linguistic images and cognitive concepts, emphasizing the role of language in shaping human perception and knowledge. Linguistic images, including visual, auditory, and metaphorical representations, serve as cognitive tools that reflect individual and cultural worldviews. The study discusses two primary cognitive approaches—logical and experimental—and highlights their significance in understanding language and cognition. Additionally, the research examines the integration of gestalt principles, prototypes, and conceptual structures in the formation of linguistic images. The findings suggest that linguistic images contribute to the organization and transmission of knowledge, shaping conceptual understanding and communicative interactions.